ASSESSMENT OF KNOWLEDGE REGARDING EARLY SIGNS OF ORAL CANCER AMONG ADULTS IN SELECTED RURAL AND URBAN COMMUNITY, WEST BENGAL - Pain, Tanuja; Mazumder, Manika; Maity, Chandrima (International Journal of Research -GRANTHAALAYAH, 2023)
Oral cancer is one of the public health problem in today’s world. It is one among the ten commonest cancers within the world. Recognition of early signs helps in early diagnosis of oral cancer and quick, successful, and less aggressive treatment or management. If the cancer is detected at an initial stage, then the 85% people can survive for 5-year. Aim: This study aims to assess the knowledge regarding early signs of oral cancer among adults in selected rural and urban community, West Bengal. Methods: A descriptive survey research was carried out with total 200 male adults aged 18 to 50 years, of selected rural and urban community, West Bengal. Data were collected through non probability purposive sampling technique. Validated structured interview schedule was used to collect data. Data were collected on adults’ demographic characteristics and knowledge regarding early signs of oral cancer. Result: The result revealed that in rural community most of the adults (50%) had average knowledge and in urban community most of the adults (37%) had good knowledge. There is significant difference between the knowledge scores among adults of rural and urban community (p<0.001). Adults of urban community are more knowledgeable than adults of rural community. Chi- square test revealed that there was a significant association of knowledge with age, educational status (p<0.001) and habit and addiction (p<0.01) of rural adults and monthly family income, habit and addiction and information received by the adults of urban community are significantly associated with their knowledge (p<0.001). Conclusion: There is the need to increase awareness in the community through educational programmes on early signs of oral cancer which will be helpful in early detection and diagnosis of same, as well as take timely precautionary measures to prevent oral cancer and thereby reducing the morbidity, mortality, and global burden of oral cancer.